2018
DOI: 10.1111/clr.13297
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of printed casts generated from digital implant impressions versus stone casts from conventional implant impressions: A comparative in vitro study

Abstract: Printed casts generated from digital impressions for partially edentulous posterior mandibular arches had inferior accuracy to conventional stone casts fabricated from splinted open tray impressions. The printed casts from WL IOS had better accuracy compared to AWST IOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 28 publications
2
60
0
2
Order By: Relevance
“…Excluded studies either did not assess full-arch dental model [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] or were not published in English [ 28 , 29 , 30 ]. Three additional studies were later removed as they assessed and compared the accuracy of different intraoral scanners [ 5 , 31 , 32 ]. In addition, one study [ 33 ] was excluded as it was a published abstract.…”
Section: Resultsmentioning
confidence: 99%
“…Excluded studies either did not assess full-arch dental model [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] or were not published in English [ 28 , 29 , 30 ]. Three additional studies were later removed as they assessed and compared the accuracy of different intraoral scanners [ 5 , 31 , 32 ]. In addition, one study [ 33 ] was excluded as it was a published abstract.…”
Section: Resultsmentioning
confidence: 99%
“…Any digital impression is generating a STL file that is further used within the whole digital workflow for virtual design and physical manufacturing of interim PMMA crowns [29][30][31][32][33]. It was found that throughout the digital flow cumulative error may arise from the optical impression to the manufacturing stage that lead to volumetric discrepancies in final milled or printed dental pieces [29,33].…”
Section: Resultsmentioning
confidence: 99%
“…There are, at the same time, some reports in the literature that are different from the results of the present study. For example, Alshawaf et al, (2018) [5] mention that, when performing fixed prosthetic restorations supported by dental implants in case of Kennedy's Class II edentations, the printed models generated after intraoral scanning have an inferior accuracy to the conventional gypsum models made after an open-tray impression. Ji-Young Sim [16] publishes a study according to which 3D printed models have a lower accuracy compared to conventional ones.…”
Section: Resultsmentioning
confidence: 99%
“…A few years ago, laboratory scanning (extraoral scanning/EO) proved to provide better accuracy for dental models than intraoral scanning/IO [1]. Even relatively recently, in the years 2017/2018, the scientific literature reported that the conventional method / traditional impression technique was still the "best solution" for performing large prosthetic restorations, respectively for fixed prosthetic restorations of the entire arch, supported on natural teeth or implants [2][3][4][5].…”
mentioning
confidence: 99%